The Relevance of Pancasila in the Development of Global Constitutionalism - Rizky Herdiansyah (Universitas Negeri Semarang, 2025)
The discourse on global constitutionalism has expanded significantly in recent decades as scholars and policymakers explore frameworks that promote human rights, the rule of law, democratic governance, and institutional accountability across diverse political systems. While this discourse has been largely shaped by Western liberal traditions, emerging scholarship increasingly acknowledges the relevance of non-Western normative systems in enriching global constitutional debates. In this context, Pancasila—as Indonesia’s foundational philosophical doctrine—presents a distinctive value framework rooted in humanity, social justice, deliberative democracy, and communal harmony. These characteristics position Pancasila as a potentially important contribution to contemporary constitutional thought, particularly in the search for more inclusive and culturally diverse models of constitutionalism. Existing studies on global constitutionalism tend to focus predominantly on the evolution of liberal constitutional principles and their diffusion into international legal norms. Only a limited number of works have examined how indigenous or non-Western philosophical systems may interact with, complement, or challenge the prevailing paradigm. Even the few studies that discuss Southeast Asian constitutional identity often center on constitutional practice rather than the underlying philosophical foundations that shape state ideology. As a result, the role of Pancasila in global constitutional discourse remains underexplored, leaving a significant gap in the literature regarding how its normative principles may contribute to the theoretical development of global constitutionalism. This article seeks to address this research gap by offering a systematic analysis of the relationship between Pancasila and the core tenets of global constitutionalism. The novelty of this study lies in its attempt to conceptualize Pancasila not merely as a national ideology but as a value framework with potential universal relevance, especially concerning human dignity, ethical governance, and the balance between individual rights and collective responsibility. By examining Pancasila through a constitutional-theoretical lens, this research aims to highlight how its emphasis on social harmony, deliberation, and moral–ethical governance can enrich the evolving discourse on global constitutional norms. To achieve these objectives, this study employs a normative–qualitative method that relies on constitutional documents, scholarly literature, and comparative constitutional perspectives. The article is structured into five main sections: the first presents the conceptual foundation of global constitutionalism; the second analyzes Pancasila’s philosophical and constitutional dimensions; the third discusses points of convergence and divergence between Pancasila and global constitutional norms; and the fourth elaborates on the implications of integrating Pancasila into global constitutional discourse. The article concludes by summarizing key findings and offering recommendations for further scholarly engagement.